Islamic Social Reporting and Financial Performance: A Bibliometric Analysis - Saaul Mufidah, Ikhdazahrotunni; Ulum, Ihyaul; Wahyu Oktavendi, Tri; Dwi Mawardi, Fahmi; Afrizal, Faris (Dinasti International Journal of Economics, Finance & Accounting, 2023)
Examining the topic of Islamic Social Reporting and Financial Performance from previous research can provide opportunities for further research that is more diverse and innovative. So, to support this research, then mapping is done by analyzing previous research with identifying and analyzing similar research that is relevant in the field of sharia accounting, which discusses the topic of Islamic Social Reporting and Financial Performance. The aim of this research is to map research that is related to the field of sharia accounting. for publication in indexed journals. Scopus, Sinta 1, Sinta 2, Sinta 3, Sinta 4, Sinta 5, Sinta 6, Garuda, and DOAJ. This research uses a type of desk research, using bibliometric analysis methods. It was found that research on Islamic social reporting and financial performance had appeared since 2012. There are 35 articles that discuss topics related to Islamic Social Reporting and Financial Performance, these 35 articles are then explained in this study. 2019 was the peak of the number of published articles related to the topic of Islamic social reporting and financial performance with the highest number of 8 articles. Based on the results of the mapping and analysis of this research, it is concluded that Islamic social reporting and financial performance research has begun to be widely studied from year to year and can be developed into topics related to sharia banking, Islamic banking, profit sharing ratios, Islamic corporate governance, and sharia compliance.